2022
DOI: 10.3389/fmicb.2022.1042944
|View full text |Cite
|
Sign up to set email alerts
|

Populus root exudates are associated with rhizosphere microbial communities and symbiotic patterns

Abstract: IntroductionMicrobial communities in the plant rhizosphere are critical for nutrient cycling and ecosystem stability. However, how root exudates and soil physicochemical characteristics affect microbial community composition in Populus rhizosphere is not well understood.MethodsThis study measured soil physiochemistry properties and root exudates in a representative forest consists of four Populus species. The composition of rhizosphere bacterial and fungal communities was determined by metabolomics and high-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…A previous study also suggested that the effect of straw return on the RA of Proteobacteria was related to the nitrogen level (Du, Zhang, et al, 2022). The sufficient air and organic nutrient conditions provided by BC might be responsible for the increase in Sphingomonas (Li, Song, et al, 2022; Li, Zheng, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study also suggested that the effect of straw return on the RA of Proteobacteria was related to the nitrogen level (Du, Zhang, et al, 2022). The sufficient air and organic nutrient conditions provided by BC might be responsible for the increase in Sphingomonas (Li, Song, et al, 2022; Li, Zheng, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The RAs of Acremonium and Trichoderma were increased by SD (at the N0 level) and BC (at the N100 level), respectively (Figure 3 and Table S2). As a well‐known plant growth‐promoting fungus, Trichoderma can activate the plant immune system against pathogens (Fernández‐González et al, 2020; Li, Song, et al, 2022; Li, Zheng, et al, 2022). Acremonium was also considered to be a beneficial fungus and was found to be dominant in soils treated with organic residues (Hernández‐Lara et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most studies have been conducted on herbaceous plants or shrubs, whereas similar studies with trees are limited to a few species and involve very few forest trees (Vives-Peris et al, 2020). To our knowledge, only one study has attempted to characterize poplar root exudates, and it focused more on rhizospheric soil metabolomes rather than on actual exudates (Li et al, 2022). Even less is known regarding feedback effects of rhizospheric microbiota on tree exudation.…”
Section: Introductionmentioning
confidence: 99%
“…Quintessentially, Microvirga species have been described as keystone taxon in biocontrol of crop diseases(Li et al, 2022;Xing et al, 2022) and equally enhance crop growth upon degrading pesticide and making nutrient available (Castellano-Hinojosa and Strauss, 2020). Abundance of Streptomyces OTUs exerts negative antagonistic interaction with microbial pathogen to confer protection to maize by suppressing root diseases.…”
mentioning
confidence: 99%